A Comparative Study on Absorbable and Non-Absorbable Suture Materials for the Closure of Skin in Rabbit Model - Saleem, Tamseel; Kachiwal, Allah Bux; Memon, Aliza; Memon, Ahsan; Memon, Fiza (Indus Journal of Bioscience Research, 2024)
Skin closure is a critical component of surgical procedures, and the selection of suture material has a significant impact on wound healing outcomes. This investigation aims to compare the effectiveness of absorbable and non-absorbable sutures for skin closure in rabbits. An experimental study was conducted on thirty (n=30) male rabbits aged 9.78+0.46 weeks and with an average weight of 1186.94+69.93 gms. Rabbits were divided into two groups, with one receiving absorbable sutures while the other received non-absorbable sutures. Wound healing parameters such as wound closure time, tensile strength, tissue reaction, and histological evaluation were evaluated over a specified period. Our findings suggest that both types of suture materials are effective in closing skin wounds in rabbits. However, absorbable sutures exhibited faster wound closure times and less tissue reaction compared to non-absorbable sutures. Conversely, non-absorbable sutures demonstrated higher tensile strength and better histological evaluations at the wound site. The results indicated significantly better wound healing with non-absorbable suture material than with absorbable suture material; indeed, there was an outstandingly high (++++) wound healing score when using non-absorbable suture material compared to that obtained from using absorbables. Moreover, rabbits recovered excellently from wounds treated with non-absorbables; thus demonstrating that choosing a specific type of suture material should be based on individual patient factors and requirements for each surgical procedure. Further studies are required to confirm these findings across larger animal models or human patients conclusively. In conclusion, it is evident that opting for non-absorbent materials results in expedited skin wound healing with superior outcomes when compared to their absorbent counterparts.